Resident Education and Virtual Medicine: A Faculty Development Session to Enhance Trainee Skills in the Realm of Telemedicine - Anna E. Rueda; Ana C. Monterrey; Margaret Wood; Linessa Zuniga; Betty Del Rio Rodriguez (Association of American Medical Colleges, 2023)
Introduction COVID-19 accelerated the use of telemedicine. Subsequently, clinical sites began conducting virtual visits. Academic institutions implemented telemedicine for patient care and simultaneously had to teach residents the logistics and best practices. To meet this need, we developed a training session for faculty focused on telemedicine best practices and teaching telemedicine in the pediatric realm. Methods We designed this training session based on institutional and society guidelines and faculty experience with telemedicine. Objectives included telemedicine documentation, triage, counseling, and ethical issues in telemedicine. We conducted all sessions in a 60-minute or 90-minute format over a virtual platform for small and large groups using case scenarios with photos, videos, and interactive questions. A novel mnemonic ABLES (awake-background-lighting-exposure-sound) was created to guide providers during the virtual exam. Following the session, participants completed a survey evaluating content and presenter effectiveness. Results We presented the training sessions between May 2020 and August 2021 to 120 participants. Participants included pediatric fellows and faculty, reaching 75 participants locally and 45 nationally (at Pediatric Academic Society and Association of Pediatric Program Directors meetings). Sixty evaluations (response rate: 50%) showed favorable results for general satisfaction and content. Discussion This telemedicine training session was well received by pediatric providers and addressed the need for training faculty to teach telemedicine. Future directions include adapting the training session for medical students and developing a longitudinal curriculum that applies telehealth skills learned with patients in real time.